2006
DOI: 10.1002/hipo.20215
|View full text |Cite
|
Sign up to set email alerts
|

Subiculum network excitability is increased in a rodent model of temporal lobe epilepsy

Abstract: In this study, we used in vitro electrophysiology along with immunohistochemistry and molecular techniques to study the subiculum--a limbic structure that gates the information flow from and to the hippocampus--in pilocarpine-treated epileptic rats. Comparative data were obtained from age-matched nonepileptic controls (NEC). Subicular neurons in hippocampal-entorhinal cortex (EC) slices of epileptic rats were: (i) hyperexcitable when activated by CA1 or EC inputs; and (ii) generated spontaneous postsynaptic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
69
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 64 publications
8
69
1
Order By: Relevance
“…Such a mechanism has been reported in the hippocampus and EC layers II/III (Bekenstein and Lothman, 1993;Williams et al, 1993;Sloviter, 1987;Doherty and Dingledine, 2001;Sloviter et al, 2003;Kumar and Buckmaster, 2006). Experiments performed in pilocarpine-treated rats have also demonstrated that pharmacologically isolated, GABA A receptor-mediated IPSPs have more positive reversal potentials in neurons recorded in vitro from the epileptic subiculum, peirhinal cortex and amygdala (de Guzman et al, 2006;Benini and Avoli, 2005;Benini et al, 2011); these data often correlated with reduced levels of mRNA expression and immunoreactivity of the neuron-specific cotransporter KCC2. In line with the view that altered homeostasis of intracellular [Cl − ] is associated with epileptogenesis, NKCC1 mRNA and proteins in the mouse CA1 subfiled are up-regulated up to 45 days following pilocarpine-induced status epilepticus, while KCC2 is down-regulated (Li et al, 2008).…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 66%
See 1 more Smart Citation
“…Such a mechanism has been reported in the hippocampus and EC layers II/III (Bekenstein and Lothman, 1993;Williams et al, 1993;Sloviter, 1987;Doherty and Dingledine, 2001;Sloviter et al, 2003;Kumar and Buckmaster, 2006). Experiments performed in pilocarpine-treated rats have also demonstrated that pharmacologically isolated, GABA A receptor-mediated IPSPs have more positive reversal potentials in neurons recorded in vitro from the epileptic subiculum, peirhinal cortex and amygdala (de Guzman et al, 2006;Benini and Avoli, 2005;Benini et al, 2011); these data often correlated with reduced levels of mRNA expression and immunoreactivity of the neuron-specific cotransporter KCC2. In line with the view that altered homeostasis of intracellular [Cl − ] is associated with epileptogenesis, NKCC1 mRNA and proteins in the mouse CA1 subfiled are up-regulated up to 45 days following pilocarpine-induced status epilepticus, while KCC2 is down-regulated (Li et al, 2008).…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 66%
“…For instance, robust periods of firing depression (presumably corresponding to IPSPs) have been recorded in electrophysiological studies performed presurgically with intracranial electrodes or extracellular unit recordings in TLE patients (Wilson and Engel, 1993;Isokawa-Akesson et al, 1989). Moreover, histochemical studies have demonstrated that some interneuron subtypes are preserved in both human and experimental animal epileptic tissue Davenport et al, 1990;Esclapez et al, 1997) even though some other subtypes are clearly decreased in number in specific limbic structures (de Guzman et al, 2006(de Guzman et al, , 2008.…”
Section: Gaba a Receptor-mediated Inhibition In Temporal Lobe Epilepsymentioning
confidence: 99%
“…The latter changes along with NMDA receptor upregulation have been reported in pilocarpine-treated parahippocampal areas such as the subiculum (Knopp et al, 2005;de Guzman et al, 2006), the EC (Kobayashi et al, 2003;Kumar and Buckmaster, 2006;Yang et al, 2006;de Guzman et al, 2008) and the lateral amygdala (LA) (Benini and Avoli, 2005). In addition, modified GABA A receptor signaling due to changes in K + /Cl − cotransporter has been identified in the epileptic human subiculum in vitro (Cohen et al, 2002;Wozny et al, 2003;Huberfeld et al, 2007).…”
Section: Introductionmentioning
confidence: 89%
“…de Guzman et al, 2006Guzman et al, , 2008. All efforts were made to minimize the number of animals used and their suffering.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation